2012
DOI: 10.3382/japr.2011-00363
|View full text |Cite
|
Sign up to set email alerts
|

Sperm production and testicular development of broiler breeder males reared on shortened growth cycles

Abstract: Primary Audience: Broiler Breeder Managers, Flock Supervisors, Researchers SUMMARYFeed restriction is an important tool used in the rearing of broiler breeders to control growth and maintain BW. Feed restriction during the growing phase typically provides 60 to 80% less feed than the birds would consume if provided feed ad libitum, resulting in a perceived animal welfare issue. Because males are typically more rigorously feed restricted than females, this is thought to be especially stressful to the growing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
1
1
1
Order By: Relevance
“…The difference of values of sperm concentration found in this study among studies by Moyle et al (2012), Mangiagalli et al (2010), andTriques et al (2016) can be justified due to the low seminal volume found by these authors.…”
Section: Resultscontrasting
confidence: 39%
“…The difference of values of sperm concentration found in this study among studies by Moyle et al (2012), Mangiagalli et al (2010), andTriques et al (2016) can be justified due to the low seminal volume found by these authors.…”
Section: Resultscontrasting
confidence: 39%
“…Faktanya, selama periode pra-pubertas, perkembangan testis sangat terkait dengan jumlah dan ukuran sel Sertoli, sementara itu, perkembangan testis berkorelasi dengan jumlah sel germinal pada periode pubertas. Hal ini sesuai dengan laporan Moyle et al (2012) melaporkan bahwa peningkatan berat testis tidak diikuti dengan peningkatan produksi spermatozoa. Testis menghasilkan spermatozoa dan plasma semen menunjukkan bahwa perkembangan testis tidak hanya terkait dengan proliferasi sel Sertoli tetapi juga dengan pembentukan aktivitas spermatogenesis (Lűpold et al 2011).…”
Section: Faktor-faktor Yang Mempengaruhi Kualitas Semen Ayamunclassified
“…Similar fertility problems are also present in the turkey industry. Although it is believed that the low fertility is associated with selection for rapid growth, broiler breeders display individual variations in sperm count and fertility (Moyle et al 2012), suggesting the potential for obtaining improved fertility by exploiting genetic diversity in the existing stock. Considering that the United States produced approximately nine billion broilers in 2017 (according to US Broiler Industry: Background Statistics and Information from USDA) at a price of $2.24 per broiler chick (according to the price on www.purelypoultry.com, March 2019), even a 1% increase in the reproductive efficiency of broiler breeders will reduce the cost of broilers by $200 million per year.…”
Section: New Pirna Acquisitionmentioning
confidence: 99%